Is Ekman pumping responsible for the seasonal variation of warm circumpolar deep water in the Amundsen Sea?. (1st January 2017) - Kim, T.W.; Ha, H.K.; Wåhlin, A.K.; Lee, S.H.; Kim, C.S.; Lee, J.H.; Cho, Y.K.
Abstract: Ekman pumping induced by horizontally varying wind and sea ice drift is examined as an explanation for observed seasonal variation of the warm layer thickness of circumpolar deep water on the Amundsen Sea continental shelf. Spatial and temporal variation of the warm layer thickness in one of the deep troughs on the shelf (Dotson Trough) was measured during two oceanographic surveys and a two-year mooring deployment. A hydrographic transect from the deep ocean, across the shelf break, and into the trough shows a local elevation of the warm layer at the shelf break. On the shelf, the water flows south-east along the trough, gradually becoming colder and fresher due to mixing with cold water masses. A mooring placed in the trough shows a thicker and warmer layer in February and March (late summer/early autumn) and thinner and colder layer in September, October and November (late winter/early spring). The amplitude of this seasonal variation is up to 60 m. In order to investigate the effects of Ekman pumping, remotely sensed wind (Antarctic Mesoscale Prediction System wind data) and sea ice velocity and concentration (EASE Polar Pathfinder) were used. From the estimated surface stress field, the Ekman transport and Ekman pumping were calculated. At the shelf break, where the warm layer is elevated, the Ekman pumping shows a seasonal variation correlating with the mooring data. Previous studies have not been able to show a correlation between observed wind and bottom temperature, but it is shown here that when sea ice drift is taken into account the Ekman pumping at the outer shelf correlates with bottom temperature in Dotson Trough. The reason why the Ekman pumping varies seasonally at the shelf break appears to be the migration of the ice edge in the expanding polynya in combination with the wind field which on average is westward south of the shelf break. Highlights: Ekman pumping induced by horizontally varying wind and sea ice drift is examined as an explanation for observed seasonal variation of the warm layer thickness of circumpolar deep water on the Amundsen Sea continental shelf. Spatial and temporal variation of the warm layer thickness in Dotson Trough was measured during two oceanographic surveys and a two-year mooring deployment. The observations were compared to time series of remotely sensed surface stress.